ACTIVE METHODOLOGIES AS A TOOL FOR MEANINGFUL LEARNING IN ELEMENTARY EDUCATION - Cinara dos Santos S. Menezes, Romeika; Simão de Carvalho, Tatiana; Dantas de S. Nunes, Eliane; Aparecida Bonifácio da S. Costa, Maria; Oneide Meneses Pina, Maria; Nicacio de Menezes, Anicleide; de Menezes Ramos, Jozilene (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the impact of active methodologies on the learning process of elementary school students. Given the limitations of traditional teaching, which focuses on memorization and the passive stance of students, the research proposes pedagogical strategies that value student protagonism and the collaborative construction of knowledge. The research, of a qualitative and exploratory nature, was carried out in a public school in Rio Grande do Norte, with the application of activities in two cycles: one with conventional practices and the other with active approaches, such as Problem-Based Learning (PBL), mind maps and thematic debates. The data were analyzed in light of authors such as Freire, Ausubel, Bacich, Piaget and Vygotsky. The results indicate that active methodologies promote greater engagement, autonomy and conceptual understanding among students, transforming the role of the teacher into a mediator of meaningful experiences. The research reinforces the importance of these practices as effective alternatives aligned with the BNCC guidelines, contributing to a more critical and participatory education.